Rapid Targeted Next-Generation Sequencing Platform for Molecular Screening and Clinical Genotyping in Subjects with Hemoglobinopathies - Shang, Xuan; Peng, Zhiyu; Ye, Yuhua; Asan; Zhang, Xinhua; Chen, Yan; Zhu, Baosheng; Cai, Wangwei; Chen, Shaoke; Cai, Ren; Guo, Xiaoling; Zhang, Chonglin; et al. (EBioMedicine, 2017)
Hemoglobinopathies are among the most common autosomal-recessive disorders worldwide. A comprehensive next-generation sequencing (NGS) test would greatly facilitate screening and diagnosis of these disorders. An NGS panel targeting the coding regions of hemoglobin genes and four modifier genes was designed. We validated the assay by using 2522 subjects affected with hemoglobinopathies and applied it to carrier testing in a cohort of 10,111 couples who were also screened through traditional methods. In the clinical genotyping analysis of 1182 β-thalassemia subjects, we identified a group of additional variants that can be used for accurate diagnosis. In the molecular screening analysis of the 10,111 couples, we detected 4180 individuals in total who carried 4840 mutant alleles, and identified 186 couples at risk of having affected offspring. 12.1% of the pathogenic or likely pathogenic variants identified by our NGS assay, which were undetectable by traditional methods. Compared with the traditional methods, our assay identified an additional at-risk 35 couples. We describe a comprehensive NGS-based test that offers advantages over the traditional screening/molecular testing methods. To our knowledge, this is among the first large-scale population study to systematically evaluate the application of an NGS technique in carrier screening and molecular diagnosis of hemoglobinopathies. •In 10,111 couples in prevention programs for thalassemia, 186 at-risk couples were identified by NGS and 151 by traditional routine method.•NGS assay had better performance than traditional routine screening approach in carrier screening for hemoglobinopathies.•NGS assay can characterize patients with Thalassemia Major or Thalassemia Intermedia more accurately. Hemoglobinopathies represent a major cause of birth defects in China. Traditional carrier screening strategy is phenotype-based that is associated with risk of miss phenotype-negative carriers. In this study, we validated an effective method for molecular screening and clinical genotyping of hemoglobinopathies using NGS assay. Considering the broad mutation spectrum and high prevalence of hemoglobinopathy-causing mutations across ethnic groups, this technology could make it technically feasible to offer more effective preconception screening and diagnosis in large populations worldwide. Therefore, the current phenotype-based screening guideline might be modified to a better genotype-based screening guideline.